IMPROVEMENT OF METHODS OF PROVIDING OUTPATIENT SURGICAL CARE IN PRIMARY HEALTH CARE (British Journal of Global Ecology and Sustainable Development, 2023)
Outpatient care is the most widespread and accessible type of medical care; it is received by about 80% of all patients who apply to healthcare organizations. The availability of outpatient care is provided by a wide network of institutions. In 2012, more than 1.1 thousand outpatient clinics functioned, in which medical care was provided to more than 10 million people.The problem of improving outpatient care for the population is a priority, strategic direction of healthcare reform at the present stage. It is outpatient care that should be a mass public form of providing medical care to the population.